2022
DOI: 10.1159/000523870
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Relieves Obesity-Induced Myocardial Injury by Regulating the Epigenetic Suppression of <b><i>miR-196b</i></b> Mediated by lncRNA HOTAIR

Abstract: <b><i>Introduction:</i></b> Obesity has been believed to be closely linked with many kinds of diseases including atherosclerosis, hypertension, cerebrovascular thrombosis, and diabetes. Ghrelin and Homeobox transcript antisense RNA (HOTAIR) were believed to be involved in the regulation of myocardial injury. <b><i>Methods:</i></b> The obesity mice model was established through feeding mice (C57BL/6J, male, eight-week-old) with high-fat diet and palmitate (PA)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Adipocyte differentiation is essential for lipid deposition in mammals [28]. It has been shown that the normal expression of the PLAAT3 gene promotes lipid deposition in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte differentiation is essential for lipid deposition in mammals [28]. It has been shown that the normal expression of the PLAAT3 gene promotes lipid deposition in mice.…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIR (HOX transcript antisense RNA) [46] and CCL11 [47] are master regulator that are activated in cardiovascular diseases. HOTAIR (HOX transcript antisense RNA) [48], SLC15A1 [49] and CRH (corticotropin releasing hormone) [50] genes might be related to the pathophysiology of obesity. HOTAIR (HOX transcript antisense RNA) [51], CCL11 [52] and CRH (corticotropin releasing hormone) [53] expression is related to the patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin, a polypeptide with cardioprotective properties, has been observed to target the lncRNA H19/miR-29a/insulin-like growth factor 1 (IGF-1) signaling pathway and the lncRNA HOTAIR/miR-196b/IGF-1 signaling pathway, thereby mitigating cardiomyocyte injury associated with obesity. 138,139 These studies not only enhance our comprehension of the mechanisms by which lncRNAs regulate obesity-associated CVDs, but also offer novel avenues and insights for future research and clinical interventions.…”
Section: Obesity-induced Lncrna Alterations On Cvdsmentioning
confidence: 99%